The Role of Prosecutors in the Juvenile Justice System Towards Recidivist Juvenile Offenders at the Semarang District Attorney's Office - Amalia, Naura; Ramada, Diandra Preludio (Universitas Negeri Semarang, 2025)
The purpose of this study is to determine the role of the prosecutor against recidivist child offenders in Decision Number 23/Pid.Sus-Anak/2024/PN Smg. The research method uses an empirical and sociological juridical approach that examines the effectiveness of the application of law through analysis of regulations, social values, and the practice of handling children's cases. The results of the study explain that the role of prosecutors in the juvenile criminal justice system against recidivist child offenders in the Semarang District Attorney's Office is very important and takes place thoroughly from the investigation stage to prosecution. Prosecutors not only carry out the prosecution function, but also actively examine the completeness of case files, evaluate the results of the litmas from Bapas, and consider psychological, social factors, and the potential for child recidivism. Prosecution is carried out proportionally with a restorative and rehabilitative justice approach, paying attention to the principle of the best interest of the child, and applying disparity in charges between recidivist and non-recidivist child offenders. Obstacles in the form of time constraints and lack of family support are challenges, but case resolution is still pursued quickly, fairly, and in favor of the protection and social recovery of children. These findings indicate the urgency of improving the handling of recidivist child offenders, which requires a more comprehensive and adaptive update of the SPPA Law, as well as the issuance of prosecutor regulations as official guidelines based on restorative justice and the principle of the best interests of the child.